Pemberian Jus Aloe Guava Terhadap Kadar Glukosa Darah Postprandial - Suryaningrum, Septiani; Prihatin, Setyo; Wijaningsih, Wiwik (Poltekkes Kemenkes Semarang, 2013)
Background : Diabetes mellitus (DM) is a metabolic disease. The early symptoms of pre diabetes can be seen in hyperglycemia postprandial. The functional food such as aloe guava juice can be given to decrease postprandial blood glucose levels. Aloe guava juice contains a substance that can increase the pancreas to produce insulin response and contains soluble fiber which can block the absorption of glucose and decrease the absorption into the blood.Objective : Knowing the effects of aloe guava juice on postprandial blood glucose levels in Semarang Polytechnic students are provided with a meal.Method : This research is an experimental sample-series, with a total sample of 10 people. All subjects receive 2 times the treatment, the first treatment subjects was fed and then an interval of 1 week of feeding subjects treated with aloe guava juice with the same amount of carbohydrate that is 55.5 grams. Methods of measurement of fasting and postprandial glucose levels using a easy touch. Test paired T-test was used to analyze the effect of aloe guava juice on postprandial blood glucose levels.Results : Based on Paired T-test, there was no significant effect of aloe guava juice at minute 0 '(p = 0.834), the 30' (p = 0.566), the 60 '(p = 0.615) and the 120' (p = 0.511), but at minute 180 ' significant effect of aloe guava juice on the postprandial blood glucose levels was detected, (p = 0.012)Conclusion : The aloe guava juice has the potency to decrease postprandial blood glucose levels after three hours.